Using analytic rating scales to assess English/Chinese bi-directional interpretation: A longitudinal Rasch analysis of scale utility and rater behavior - Han, Chao (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
Descriptor-based analytic rating scales have been increasingly used to assess interpretation quality. However, little empirical evidence is available to unequivocally support the effectiveness of rating scales and rater reliability. This longitudinal study thus attempts to shed insight into scale utility and rater behavior in English/Chinese interpretation performance assessment, using multifaceted Rasch measurement. Specifically, the study focuses on criterion/scale difficulty, scale effectiveness, rater severity/leniency and rater self-consistency between English/Chinese interpreting and over three time points. Research results are discussed, highlighting the utility of analytic rating scales and the variability of rater behavior in interpretation assessment. The results also have implications for developing reliable, valid, and practical instruments to assess interpretation quality.